2021
DOI: 10.1016/j.celrep.2021.109306
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear kinesin KIF18B promotes 53BP1-mediated DNA double-strand break repair

Abstract: Highlights d KIF18B, a nuclear kinesin, is required for efficient end-joining of DSBs d A Tudor-interacting motif (TIM) in KIF18B directly interacts with the 53BP1 Tudor d KIF18B's TIM facilitates the binding of 53BP1 to chromatin in the vicinity of DSBs d The motor activity KIF18B is also required for efficient 53BP1 recruitment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 52 publications
(78 reference statements)
0
22
0
Order By: Relevance
“…As discussed, its role in slow-kinetic cNHEJ is not just limited to inhibition of resection but it may also have active roles in slowkinetic cNHEJ (e.g., recruitment of Artemis, CST-Polα-primase), while in HR 53BP1 promotes fidelity by preventing excessive resection (Wang et al, 2014;Ochs et al, 2016;Löbrich and Jeggo, 2017;Mirman et al, 2018;Zhao et al, 2020;Kelich et al, 2021). Given such important roles, it is not surprising that 53BP1 recruitment is tightly regulated by multiple additional mechanisms: 1) the Tudor interacting repair regulator (TIRR) can bind the Tudor domain of 53BP1 to block its H4K20me2 binding (Drané et al, 2017;Dai et al, 2018;Wang et al, 2018); 2) acetylation within the 53BP1 UDR domain (K1626/K1628) by CREB-binding protein (CBP) disrupts 53BP1 binding to the nucleosome (Guo et al, 2018); 3) RNF169, an RNF168 paralogue, appears to be able to antagonise 53BP1, as well as RAP80-BRCA1, accumulation at DSBs through a mechanism that remains enigmatic (Chen et al, 2012;Panier et al, 2012;Poulsen et al, 2012;An et al, 2018); 4) phosphorylation of the damage dependent H2AK15 ubiquitin tag (UbT12p) itself also inhibits binding of 53BP1, but not HR factors (Walser et al, 2020); intriguingly, and in contrast to these negative regulatory mechanisms, 53BP1 binding can be positively regulated by the kinesin, KIF18B, in a mechanism requiring a direct interaction with the 53BP1 Tudor domain and the motor activity of KIF18B (Luessing et al, 2021).…”
Section: The Role Of 53bp1 and Brca1 In The Late Double Strand Break Responsementioning
confidence: 99%
“…As discussed, its role in slow-kinetic cNHEJ is not just limited to inhibition of resection but it may also have active roles in slowkinetic cNHEJ (e.g., recruitment of Artemis, CST-Polα-primase), while in HR 53BP1 promotes fidelity by preventing excessive resection (Wang et al, 2014;Ochs et al, 2016;Löbrich and Jeggo, 2017;Mirman et al, 2018;Zhao et al, 2020;Kelich et al, 2021). Given such important roles, it is not surprising that 53BP1 recruitment is tightly regulated by multiple additional mechanisms: 1) the Tudor interacting repair regulator (TIRR) can bind the Tudor domain of 53BP1 to block its H4K20me2 binding (Drané et al, 2017;Dai et al, 2018;Wang et al, 2018); 2) acetylation within the 53BP1 UDR domain (K1626/K1628) by CREB-binding protein (CBP) disrupts 53BP1 binding to the nucleosome (Guo et al, 2018); 3) RNF169, an RNF168 paralogue, appears to be able to antagonise 53BP1, as well as RAP80-BRCA1, accumulation at DSBs through a mechanism that remains enigmatic (Chen et al, 2012;Panier et al, 2012;Poulsen et al, 2012;An et al, 2018); 4) phosphorylation of the damage dependent H2AK15 ubiquitin tag (UbT12p) itself also inhibits binding of 53BP1, but not HR factors (Walser et al, 2020); intriguingly, and in contrast to these negative regulatory mechanisms, 53BP1 binding can be positively regulated by the kinesin, KIF18B, in a mechanism requiring a direct interaction with the 53BP1 Tudor domain and the motor activity of KIF18B (Luessing et al, 2021).…”
Section: The Role Of 53bp1 and Brca1 In The Late Double Strand Break Responsementioning
confidence: 99%
“…Kinesin family member 18B (KIF18B) is another member of kinesin that localizes to the nucleus and binds to chromatin throughout the interphase [149]. Most recently, KIF18B, which is also recruited to the sites of DSBs, was reported to be required for 53BP1-mediated DSB repair [150]. This study demonstrated that the ability of KIF18B to bind 53BP1, as well as its motor function is required for efficient 53BP1-mediated end-joining of DSBs.…”
Section: Kif18bmentioning
confidence: 92%
“…Since microtubules and kinesins have been linked to the repair of DSBs 12,14 , we sought to determine if MAP7 and MAP7D1 affect the repair of DNA damage caused by γ-irradiation.…”
Section: Downregulation Of Map7 and Map7d1 Leads To Defects In Dna Re...mentioning
confidence: 99%
“…Moreover, KIF18B and KIF2C, two kinesins which act as motor proteins on microtubules, are involved in DSB repair 14,15 . Nevertheless, the scale of processes through which microtubules affect DDR, the number of cytoskeleton-related proteins involved in DDR and the exact molecular mechanisms behind these processes remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%